Early BMI Change, Cognitive Decline, and CSF AD Biomarkers Alterations in Parkinson's Disease - Rui Zhong; Kezhong Zhang (Annals of Clinical and Translational Neurology)
ABSTRACT Objective To examine the relationship of early BMI change with subsequent cognitive decline, CSF AD biomarkers alterations, and progression to dementia in patients with PD. Methods Study data were prospectively collected from the PPMI cohort. Weight/height data at enrollment and second‐year clinical visit were utilized to calculate BMI change. Cognitive tests and CSF AD biomarkers were measured at enrollment and each visit during the 5‐year follow‐up. Generalized linear mixed analyses were employed to identify the impact of BMI change on the deterioration of cognitive performance and CSF AD biomarkers alterations. Cox regression analyses were employed to assess the relationship of BMI change with dementia conversion. Results BMI loss predicted a more rapid deterioration in global cognitive performance over time. Regarding specific cognitive domains, participants in the BMI loss group experienced a significantly more rapid decline in verbal episodic memory, language, and processing speed/attention compared with those in the stable BMI group. Additionally, patients in the BMI gain group showed a slower decline in verbal episodic memory than those in the stable BMI group. BMI loss predicted a more rapid longitudinal decrease of CSF Aβ42 over time. BMI change was not associated with the risk of progression to dementia. Conclusions Early BMI loss is a risk factor for faster decline in cognition and longitudinal decrease of CSF Aβ42. These findings emphasize the need to monitor early BMI change in PD patients. Attention to early BMI change may help identify those at greater risk of cognitive decline.